Evaluation of how different implementation strategies of an injury prevention programme (FIFA 11+) impact team adherence and injury risk in Canadian female youth football players: a cluster-randomised trial. Issue 8 (13th March 2013) - Steffen, Kathrin; Meeuwisse, Willem H; Romiti, Maria; Kang, Jian; McKay, Carly; Bizzini, Mario; Dvorak, Jiri; Finch, Caroline; Myklebust, Grethe; Emery, Carolyn A
Abstract : Background: Injury prevention programme delivery on adherence and injury risk, specifically involving regular supervisions with coaches and players on programme execution on field, has not been examined. Aim: The objective of this cluster-randomised study was to evaluate different delivery methods of an effective injury prevention programme (FIFA 11+) on adherence and injury risk among female youth football teams. Method: During the 4-month 2011 football season, coaches and 13-year-old to 18-year-old players from 31 tier 1–3 level teams were introduced to the 11+ through either an unsupervised website ('control') or a coach-focused workshop with ('comprehensive') and without ('regular') additional supervisions by a physiotherapist. Team and player adherence to the 11+, playing exposure, history and injuries were recorded. Results: Teams in the comprehensive and regular intervention groups demonstrated adherence to the 11+ programme of 85.6% and 81.3% completion of total possible sessions, compared to 73.5% for teams in the control group. These differences were not statistically significant, after adjustment for cluster by team, age, level and injury history. Compared to players with low adherence, players with high adherence to the 11+ had a 57% lower injury risk (IRR 0.43, 95% CI 0.19 to 1.00). However, adjusting for covariates, this between-group difference was not statistically significant (IRR=0.44, 95% CI 0.18 to 1.06). Conclusion: Following a coach workshop, coach-led delivery of the FIFA 11+ was equally successful with or without the additional field involvement of a physiotherapist. Proper education of coaches during an extensive preseason workshop was more effective in terms of team adherence than an unsupervised delivery of the 11+ programme to the team. Trial registration: ISRCTN67835569.